PRINSIP-PRINSIP GOOD GOVERNANCE PADA PENGELOLAAN ZAKAT DALAM PERSPEKTIF QARDHAWI: Studi pada Baitul Mal Kabupaten Aceh Tengah - Fitrah, Iwan (Fakultas Syariah, 2017)
The existence of various problems in the implementation of zakat management in the zakat organizations originated from the problem concerning some things called the principles of good governance. So to overcome the problems is by strengthening those principles. This study aims to describe the principles of good governance in the zakat management of Baitul Mal Central Aceh District on Qardhawi perspective. The analysis method used is descriptive-qualitative, with case study research strategy. Data collected through interviews, observation, and documentation. The results show that the principles of shariah, trust, equity, and participation have been going well, but the shariah principle implementation becomes constrained when facing the mechanism of zakat as Regional Original Revenue. Principles of accountability and transparancy have been implemented, but still do not use a more adequate system. Furthermore, the zakat management is still inefficient because amil funds still exceed the provisions, and also there is no amil standarization regarding the relevant educational background with zakat to support the zakat management professionally.